DOI: 10.33915/etd.7152
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Management of Golden-Winged Warblers (Vermivora Chrysoptera) and Associated Avian Species in the Allegheny Mountains of West Virginia

Abstract: This dissertation focuses on the breeding season ecology and management of Goldenwinged Warblers (Vermivora chrysoptera) in the Allegheny Mountains of West Virginia with implications for other disturbance-dependent avian species. Golden-winged Warblers have a complex life history, requiring dynamic forest landscapes with varying age classes for breeding. Populations breeding in the Appalachian Mountains are among the most rapidly decreasing among vertebrates in eastern North America. For these reasons, much re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 112 publications
3
10
0
Order By: Relevance
“…1.3 | The findings of strong total reproductive isolation are not compatible with previous work Toews et al (2021) 2021) refer to (Figure 1). We note that the pattern observed by Bennett et al (2017) has been found in other areas of sympatry (e.g., Aldinger, 2018).…”
Section: Extra-pair Paternity Is Very High In Vermivora Likely Facilitating Hybridizationsupporting
confidence: 73%
See 1 more Smart Citation
“…1.3 | The findings of strong total reproductive isolation are not compatible with previous work Toews et al (2021) 2021) refer to (Figure 1). We note that the pattern observed by Bennett et al (2017) has been found in other areas of sympatry (e.g., Aldinger, 2018).…”
Section: Extra-pair Paternity Is Very High In Vermivora Likely Facilitating Hybridizationsupporting
confidence: 73%
“…2021) refer to (Figure 1). We note that the pattern observed by Bennett et al (2017) has been found in other areas of sympatry (e.g., Aldinger, 2018).…”
Section: Extra-pair Paternity Is Very High In Vermivora Likely Facilitating Hybridizationsupporting
confidence: 73%
“…This is supported by past research on aspen forests in our study region, where Golden‐winged Warblers only persisted in sapling‐sized stands when patches of shrubby habitat with relatively open canopy occurred within the stand (Roth & Lutz, 2004). The importance of heterogeneous microhabitat conditions (e.g., early‐successional patches within otherwise more advanced successional sites) has also been found in high‐elevation pastures in the Appalachian Mountains, where Golden‐winged Warbler populations persisted for up to 33 years posttreatment, though density peaked much earlier (Aldinger, 2018). Given that monitoring in this study focused only on the first few years after treatment, it is highly likely that we lacked sufficient temporal variation to capture species responses to the effect of growing season progression.…”
Section: Discussionmentioning
confidence: 93%
“…Phenotypic pairing frequencies and pairing success rates were monitored at 14 sites during 2008–2014 in grazed pastures described by Aldinger et al., 2014, Aldinger, 2018. Sites were at 800–1,000 m elevation in Randolph County and at 700–1,250 m in Pocahontas County.…”
Section: Methodsmentioning
confidence: 99%